Human Resource Management Practices and Job Satisfaction: Evidence from Private Hospitals of Kathmandu Valley - Bhandari, Dilli Ram; Subedi, Dhruba Prasad (Journal of Emerging Management Studies, 2024)
Purpose - The purpose of this study is to examine the relationship between human resource management practices and employee job satisfaction in private hospital of Kathmandu valley. When evaluating human resource management practices, the present paper takes in to account four relevant variables namely recruitment and selection; training and development; performance appraisal and compensation and benefits, and explores their link with job satisfaction of paramedic employees. Design/methodology/approach - In order to test the relationship between human resource management practices and employee satisfaction, the descriptive and causal-comparative research designs were used. The data were collected from 384 paramedic employees on structured questionnaire through e-mail, Facebook messenger and personal contact. The study applied convenience sampling technique to collect the data. Both descriptive and inferential statistical tools were used for data analysis. Findings and Conclusion - This study revealed that all the four variables i.e. recruitment and selection; training and development; performance appraisal and compensation and benefits were the important predictors of job satisfaction. It was also found that compensation and benefits were more important for job satisfaction of the employees followed by training and development. It delved into the HRM practices tailored to private hospitals in the Kathmandu valley, highlighting their impact on the job satisfaction of paramedic staff, a relatively underexplored group in healthcare research. Practical implications- Effective Human Resource Management practices in private hospitals of the Kathmandu valley significantly impact the job satisfaction of paramedic employees, with profound practical implications. The implementation of effective HR practices can lead to higher quality patient care, increased operational efficiency, and a resilient workforce capable of effectively responding to healthcare challenges. Originality/Value- This study provides new insights into the relationship between human resource management practices and employee job satisfaction in private hospital of Kathmandu valley. To the authors’ knowledge, it was the first conceptual model developed and tested specifically for paramedic employees in this context.